Social and Behavioral Determinants of Perceived Insufficient Sleep - Grandner, Michael A.; Jackson, Nicholas J.; Izci-Balserak, Bilgay; Gallagher, Rebecca A.; Murray-Bachmann, Renee; Williams, Natasha J.; Patel, Nirav P.; Jean-Louis, Girardin (Frontiers in Neurology, 2015)
Background: Insufficient sleep is associated with cardiometabolic disease and poor health. However, few studies have assessed its determinants in a nationally-representative sample. Methods: Data from the 2009 Behavioral Risk Factor Surveillance System (BRFSS) was used (N=323,047 adults). Insufficient sleep was assessed as insufficient rest/sleep over 30 days. This was evaluated relative to sociodemographics (age, sex, race/ethnicity, marital status, region), socioeconomics (education, income, employment, insurance), health behaviors (diet, exercise, smoking, alcohol), and health/functioning (emotional support, BMI, mental/physical health). Results: Overall, insufficient sleep was associated with being female, White or Black/African-American, unemployed, without health insurance, and not married; decreased age, income, education, physical activity; worse diet and overall health; and increased household size, alcohol, and smoking. Conclusion: These factors should be considered risk factors for insufficient sleep.